2011
DOI: 10.1097/aud.0b013e31820c81b0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extreme Tonotopic Mismatches Between Bilateral Cochlear Implants on Electric Pitch Perception: A Case Study

Abstract: Pitch perception was studied in a subject with a 10-mm cochlear implant (CI) in one ear and a 24-mm CI in the other ear. Both processors were programmed to allocate information from the same frequency range of 188-7938 Hz, despite the large differences in putative insertion depth and stimulated cochlear locations between the CIs. After 2 and 3 years of experience, pitch-matched electrode pairs between CIs were aligned closer to the processor-provided frequencies than to cochlear position. This finding suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
4
35
1
Order By: Relevance
“…However, not all patients adapt to reduce this mismatch. Bimodal CI users are more likely to experience no changes in pitch or even a drop in pitch for all electrodes, exacerbating the mismatch (Reiss et al 2007(Reiss et al , 2011(Reiss et al , 2012a; consistent with this finding, several long-term studies also found electrode pitch to be mismatched to and lower than the frequency-toelectrode allocations (e.g., Blamey et al 1996;Dorman et al 2007). For bimodal CI users, it is possible that instead of or in addition to adapting pitch, the brain adapts BSI to increase fusion of interaurally mismatched inputs to effectively reduce the perception of mismatch.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, not all patients adapt to reduce this mismatch. Bimodal CI users are more likely to experience no changes in pitch or even a drop in pitch for all electrodes, exacerbating the mismatch (Reiss et al 2007(Reiss et al , 2011(Reiss et al , 2012a; consistent with this finding, several long-term studies also found electrode pitch to be mismatched to and lower than the frequency-toelectrode allocations (e.g., Blamey et al 1996;Dorman et al 2007). For bimodal CI users, it is possible that instead of or in addition to adapting pitch, the brain adapts BSI to increase fusion of interaurally mismatched inputs to effectively reduce the perception of mismatch.…”
Section: Introductionsupporting
confidence: 62%
“…For Hybrid CI users, electrode pitch perception changes relative to contralateral acoustic pitch over time, and the changes tend to occur in the direction of reducing perceived interaural pitch mismatch (Reiss et al 2007(Reiss et al , 2011. Analogous adaptations in auditory or visual receptive fields have been reported in response to auditory-visual mismatch, such as after months of experience with displacing prisms in the barn owl (Knudsen 2002) or on the time scale of seconds with the ventriquolism aftereffect (Recanzone 1998).…”
Section: Dichotic Fusion Rangesmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, the results of previous studies on the effect of electrode array length have been controversial [Boyd, 2011;Esquia Medina et al, 2013;Holden et al, 2013]. While some authors argue against short electrode arrays compromising auditory outcome [Reiss et al, 2011[Reiss et al, , 2014, others have reported higher speech perception outcome with longer electrode arrays, with subsequent residual hearing preservation [Esquia Medina et al, 2013;Usami et al, 2011].…”
Section: Introductionmentioning
confidence: 96%
“…Frequency allocation maps of cochlear implants are rarely adapted to either the insertion depth of electrode arrays or the individual variations in cochlear size. Such lack of adaptation may result in disagreement between the implant's frequency allocation map and the characteristic frequency of the auditory neurons in closest vicinity to each electrode contact [Baumann et al, 2011;Blamey et al, 1996;Boex et al, 2006;Di Nardo et al, 2010;McDermott et al, 2009;Reiss et al, 2011].…”
Section: Introductionmentioning
confidence: 99%